Intermolecular electron transfer states of 1-methyl-3-(N-(1, 8-naphthalimidyl)ethyl)imidazolium iodide obtained by constrained density functional theory. Issue 27 (25th May 2016) - Otsuka, Takao; Sumita, Masato; Izawa, Hironori; Morihashi, Kenji
Abstract : Nonradiative decay from the ET-excited state of MNEI-I is mediated by the interaction of the iodine atom with the 1, 8-naphthalimide or imidazolium groups. Abstract : Electron transfer (ET) states of 1-methyl-3-( N -(1, 8-naphthalimidyl)ethyl)imidazolium iodide are responsible for its photophysics. Investigation of an ET state based on constrained density functional theory (CDFT) revealed that nonradiative decay from the ET excited state is mediated by the interaction of the iodine atom with the 1, 8-naphthalimide or the imidazolium group.